Improving the pharmacokinetics, biodistribution and plasma stability of monobodies - Dinh-Fricke, Adrian Valentin; Hantschel, Oliver (Frontiers in Pharmacology, 2024)
Cancer is a leading cause of death worldwide. Several targeted anticancer drugs entered clinical practice and improved survival of cancer patients with selected tumor types, but therapy resistance and metastatic disease remains a challenge. A major class of targeted anticancer drugs are therapeutic antibodies, but their use is limited to extracellular targets. Hence, alternative binding scaffolds have been investigated for intracellular use and better tumor tissue penetration. Among those, monobodies are small synthetic protein binders that were engineered to bind with high affinity and selectivity to central intracellular oncoproteins and inhibit their signaling. Despite their use as basic research tools, the potential of monobodies as protein therapeutics remains to be explored. In particular, the pharmacological properties of monobodies, including plasma stability, toxicity and pharmacokinetics have not been investigated. Here, we show that monobodies have high plasma stability, are well-tolerated in mice, but have a short half-life in vivo due to rapid renal clearance. Therefore, we engineered monobody fusions with an albumin-binding domain (ABD), which showed enhanced pharmacological properties without affecting their target binding: We found that ABD-monobody fusions display increased stability in mouse plasma. Most importantly, ABD-monobodies have a dramatically prolonged in vivo half-life and are not rapidly excreted by renal clearance, remaining in the blood significantly longer, while not accumulating in specific internal organs. Our results demonstrate the promise and versatility of monobodies to be developed into future therapeutics for cancer treatment. We anticipate that monobodies may be able to extend the spectrum of intracellular targets, resulting in a significant benefit to patient outcome.